Enhanced vitamin K expenditure as a major contributor to vitamin K deficiency in COVID-19 - Visser, Margot P J; Walk, Jona; Vermeer, Cees; Bílková, Simona; Janssen, Rob; Mayer, Otto (International journal of infectious diseases, 2022)
OBJECTIVES: Vitamin K deficiency consistently associates with worse clinical outcome in COVID-19 patients. However, whether this is due to increased expenditure during inflammation or poor vitamin K status prior to infection remained unknown. METHODS: Dp-ucMGP levels of 128 individuals were measured for the post-MONICA study and were compared to SARS-CoV-2 PCR testing results. RESULTS: Dp-ucMGP levels prior to COVID-19 infection were not significantly different comparing PCR-negative, PCR-positive and not hospitalized, and PCR-positive and hospitalized patients. CONCLUSION: In this study, we demonstrate normal vitamin K status prior to infection in SARS-CoV-2 positive patients, supporting the theory of increased utilisation during disease.
Keywords: Vitamin K Deficiency; Humans; extracelulární matrix - proteiny; vitamin K; Calcium-Binding Proteins; Elastic fibers; lidé; Biomarkers; nedostatek vitaminu K; Extracellular Matrix Proteins; Matrix Gla Protein; COVID-19; biologické markery; proteiny vázající vápník; Health Expenditures; výdaje na zdravotnictví; Vitamin K; Dp-ucMGP; SARS-CoV-2